The mean cell volume difference (dMCV) reflects serum hypertonicity in diabetic dogs - Norris, Olga Chesnokova (Kansas State University, 2019)
Serum hypertonicity may develop during diabetes mellitus due to hyperglycemia and other biochemical changes. Hypertonicity may produce detrimental cellular and systemic effects and has been identified as a serum marker for some clinical disorders. In non-diabetic dogs, the mean cell volume difference, a novel erythrocyte measure, is increased by serum hypertonicity. However, it is not known whether hyperglycemic hypertonicity produces a similar change. The hypothesis that the mean cell volume difference could detect serum hypertonicity in diabetes was investigated in a group of thirty-two dogs with naturally-occurring diabetes mellitus that were prospectively recruited over a 1-year period from the outpatient population of a veterinary teaching hospital. The effect of hyperglycemia on the mean cell volume difference and the ability of the mean cell volume difference to predict serum hypertonicity were examined. Serum hyperosmolality and hypertonicity due to hyperglycemia was present in 91% and 94% of dogs, respectively. Hyperglycemia was the principal cause identified for serum hypertonicity and hyperosmolality. Using a cut-off value of > 3 μm³ for the mean cell volume difference, serum hypertonicity > 320 mmol/kg was identified with 79% sensitivity and 61% specificity. The dMCV correlated with changes in serum glucose, tonicity, and measured osmolality. Dogs with a mean cell volume difference > 3 μm³ were at risk for serum tonicity > 320 mmol/kg (risk ratio = 2.2) and serum glucose > 13.9 mmol/L (risk ratio = 2.3). In conclusion, the mean cell volume difference is a useful surrogate marker for detecting serum hypertonicity in diabetic dogs and elevated mean cell volume difference is associated with increased risks for clinically relevant serum hypertonicity and hyperglycemia.
Keywords: tonicity; diabetes mellitus; canine; endocrinology; osmolality; veterinary medicine